A study of the morbidity pattern among the elderly population in Vadodara, Gujarat - Jadav, Pranay A.; Bavarva, Neha R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Aging is an inevitable process. Old age persons are more vulnerable to physical and social problems. The objective was to study the prevalence of health problems among elderly population. Methods: A cross-sectional study was carried out on 600 old age persons living in villages of Vadodara district. Their socio-demographic profile and morbidity pattern were assessed by face to face interview. Data were analysed by epi info version 7. Results: Around 65% of study participants have musculoskeletal problems; obesity was prevalent in 46.2% which was more in females (53%) than in males (41%). Depression was more in females 76.2% as compared to males (40%). Prevalence of diabetes and hypertension were 18.7% and 30.33% respectively. Conclusions: Present study reveals that old age persons from various health problems which show the need for comprehensive health programs especially for elderly population.